Digital preservation of Rumah Tukang Kahar for cultural heritage tourism - Aiman Mohd Rashid; Lisa Sidyawati; Nor Izura Tukiman; Norhaida Mohd Suaib; Mohd Farid Mohd Ariff (Department of Architecture Faculty of Engineering Universitas Indonesia, 2023)
The paper focuses on exploring the virtual collaboration process in the digital preservation project of Rumah Tukang Kahar, a traditional Malay house in Negeri Sembilan, Malaysia, as a form of cultural heritage tourism. The purpose of the project is to develop an augmented reality interface through mobile app, website, and pamphlets with AR markers, to virtually and physically boost Malaysia heritage tourism economy. This paper describes a year-long virtual collaboration process between multidisciplinary and transnational researchers with various expertise between Malaysia and Indonesia under the Indonesia-Malaysia Research Consortium (I'MRC) initiatives. The paper reflects on the design and product development process and challenges within the virtual collaboration between two universities. The researchers’ involvement in the virtual collaboration process suggests that effective asynchronous and synchronous communication using online textual and visual communication tools and platforms leads to more effective, productive, and meaningful outcomes in research, collaboration, and product development.